Transformasi Peran Kiai dalam Politik Indonesia dari Otoritas Keagamaan ke Ranah Politik Praktis - Haliza Rizqica Fadillah; Juliansyah Aditya Rahadian; Moch. Faisal Rais; Milana Sapta Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
Kiai have a central role in society which makes the figure of kiai highly respected and respected in society. The expertise that a kiai has is what makes him a central figure in the public's attention and a kiai who has many people who trust him. On the other hand, politicians who need the masses to gain votes of support often approach kiai to ask for advice or even ask for support from kiai because they see kiai who have a large mass. The aim of this research is to see the transformation of the role of kiai, who were initially as religious actors and are now becoming practical political figures. In writing this article the author used a qualitative descriptive method with literature and document studies. It can be concluded from this research that the role of kiai, which previously was only as a religious figure, has now spread to become a practical political figure. This research seeks to explain the transformation of the role of kiai and also the impacts resulting from this transformation.